Konversi Termal Kayu Ketapang (Terminalia Catappa) Menjadi Bio-Oil Dengan Teknologi Pirolisis Menggunakan Katalis Ni/Lempung - Yopalim Zanstra; Syaiful Bahri; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This research aims to produce bio-oil from ketapang (Terminalia catappa) as an alternative fuel. Variables studied the effect of the weight ratio of the catalyst Ni / clay to the biomass, the influence of the metal impregnation Nickel (Ni) on clay and characterization of physical and chemical properties of bio-oil produced. Pyrolysis process carried out at a temperature of 320°C, silinap 500 ml, 50 grams of biomass with + 100-200 mesh sieve size, variations in the catalyst Ni / clay to the biomass of 3%, 6% and 9% by weight and the variation of Ni metal Impregnation against Clay at 0% , 1%, 2%, 3%. The results was analyzed by using Gas Chromatography Mass Spectroscopy (GCMS) and showed the largest yield of bio-oil on the use of catalyst Ni/clay 6% by weight of the metal content of 3% at 71,1%. The physical properties characterization of bio-oil were obtained 0.79 g/ml for density, 2.1982 cSt for viscosity , 68.193 mg NaOH/g sample for acidity and 54oC for flash point. For the chemical properties characterization of bio-oil were obtained some dominant chemical components such as acetic acid , 2-propanone , glycidol, and 1-Hydroxy-3-sulpho-6-aminonapthalene.Keywords : Bio-Oil,Catalyst Ni/Clay,Ketapang,GCMS,Pyrolysis.